The raft - Bodeen, S. A. (Feiwel and Friends, 2012)
Robbie's last-minute flight to the Midway Atoll proves to be a nightmare when the plane goes down in shark-infested waters. Fighting for her life, the co-pilot Max pulls her onto the raft, and that's when the real terror begins.